The chemistry and physics of engineering materials. Volume 1, - Berlin, Al. Al., 1940-; Joswik, Roman; Vatin, Nikolai I.; Haghi, A. K.; Zaikov, G. E. 1935- (Apple Academic Press, 2016)
This new volume focuses on modern analytic methodologies in the chemistry and physics of engineering materials that have potential for applications in several disciplines of engineering and science. Contributions range from new methods to novel applications of existing methods. The collection of topics in this volume reflects the diversity of recent advances in chemistry and physics of engineering materials with a broad perspective that will be useful for scientists as well as for graduate students and engineers. This new book presents leading-edge research from around the world. Topics in the b.
Keywords: Materials -- Mechanical properties.; Strength of materials.; Metallurgical analysis.; Polymers -- Structure.; Chemistry, Technical.; elektronické knihy; electronic books